The Function of Blame - (:unkn) unknown (My University, 2015)
This paper sets forth a theory of blame. Many currently proposed theories of blame fail to capture all instances of blame. This motivates a pluralism about blame, suggesting that there are many kinds of blame. These varieties of blame are nonetheless united in serving a particular function in our interpersonal decision making. This function is to flag the blamed behavior in such a way as to unsure that we factor it into future interactions with the blamed person. Thus any feature of our psychology that generally fulfills this function is a kind of blame. Since on this theory an instance of blame can count as such even if it does not fulfill the function of flagging in that particular instance, as long as it is still is a kind of blame, this theory can account for virtually all cases of blame.
Keywords: Blame